One‐Pot Chemoenzymatic Cascade for Labeling of the Epigenetic Marker 5‐Hydroxymethylcytosine. Issue 13 (27th July 2015) - Nifker, Gil; Levy‐Sakin, Michal; Berkov‐Zrihen, Yifat; Shahal, Tamar; Gabrieli, Tslil; Fridman, Micha; Ebenstein, Yuval
Abstract The epigenetic DNA modification 5‐hydroxymethylcytosine (5‐hmC) is important for the regulation of gene expression during development and in tumorigenesis. 5‐hmC can be selectively glycosylated by T4 β‐glucosyltransferase (β‐GT); introduction of an azide on the attached sugar provides a chemical handle for isolation or fluorescent tagging of 5‐hmC residues by click chemistry. This approach has not been broadly adopted because of the challenging synthesis and limited commercial availability of the glycosylation substrate, 6‐deoxy‐6‐azido‐α‐D‐glucopyranoside. We report the enzyme‐assisted synthesis of this precursor by the uridylyltransferase from Pasteurella multocida (PmGlmU). We were able to directly label 5‐hmC in genomic DNA by an enzymatic cascade involving successive action of PmGlmU and β‐GT. This is a facile and cost‐effective one‐pot chemoenzymatic methodology for 5‐hmC analysis.